Spatial-temporal evolution of land ecological health and influencing factors in China's ecological civilization pilot area - Fan, Zhenggen; Liu, Binghua; Zhong, Peng (Journal of Environmental Engineering and Landscape Management, 2025)
It is crucial to assess the land ecosystem health (LEH) in China’s national pilot zones (NPZ) for ecological conservation and identify the primary factors that impact it. This is crucial for developing China’s ecological civilization and fostering sustainable, eco-friendly economic development. The study utilizes the pressure-state-response (PSR) and environment-economy-society (EES) model, relying on the panel data of 11 cities of Jiangxi in the NPZ for ecological conservation from 2005 to 2020, measuring the LEH in the national ecological civilization pilot zone using the comprehensive index evaluation method. The main contribution of this study is to optimize the land ecological health index system, construct an improved PSR-NES theoretical model that is more suitable for NPZ, reveal the spatial and temporal evolution characteristics of LEH in NPZ from the city scale, and refine the key driving factors. Results show that (1) The LEH exhibited a general shift from a state of “less healthy” level to the “healthier” level; (2) Differences in LEH evolution in different cities. The overall trend of “north to south and east to west” is gradually improving. (3) Urbanization has a strong role in the promotion of LEH, and economic development shows a significant dampening effect.